Manufacturing method of nano copper powder

The described method efficiently produces high-quality, uniformly distributed nano copper powder under mild conditions, addressing production challenges and enabling applications in various industrial fields.

KR103040520B1Active Publication Date: 2026-10-30HOJEONABLE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020250177159
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-11-20
Publication Date
2026-10-30
Estimated Expiration
2045-11-20

AI Technical Summary

Technical Problem

Existing methods for manufacturing nano copper powder face challenges in producing high-quality, uniformly distributed nano-sized copper powder efficiently and under mild reaction conditions.

Method used

A method involving an aqueous solution comprising a copper precursor, a copper ion complexing agent, a nonionic surfactant, a reaction activator from group 16 elements, and a reducing agent is used to produce nano copper powder by reacting these components in controlled temperature and time conditions.

Benefits of technology

This method enables the efficient production of high-quality nano copper powder with uniform particle distribution and high yield under mild conditions, suitable for applications in conductive pastes, electronic components, heat dissipation, electromagnetic shielding, and catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112025130276257-PAT00001_ABST
    Figure 112025130276257-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing nano copper powder capable of efficiently producing high-quality copper powder controlled to nano size. In one embodiment, the manufacturing method can achieve a high reaction rate under mild reaction conditions and can provide nano copper powder having a uniform particle distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing nano-sized copper powder. Background Technology

[0002] Copper powder is an important material widely used in various industrial fields. In particular, due to its excellent electrical and thermal conductivity, it has established itself as an essential material in electronic devices, batteries, conductive pastes, and catalysts. Traditionally, copper has been primarily used in wires, electrical circuits, and electrical contact materials, and thanks to its excellent electrical conductivity, it has played a key role in many industrial sectors.

[0003] Nano copper powder offers advantageous properties for various applications due to its large surface area and excellent physical and chemical reactivity. Copper powder manufactured at the nanoscale exhibits high reactivity and catalytic activity, and tends to show improved conductivity and mechanical properties. Such nano copper powder can play an important role, particularly in conductive pastes for wiring and electronic components in Heterojunction Technology (HJT) solar cells, heat dissipation and bonding pastes for power semiconductors in electric vehicles, via-fill pastes for glass substrates in next-generation semiconductors, electromagnetic shielding, energy storage systems (ESS), and catalysts. The problem to be solved

[0004] One aspect of the present invention provides a method for manufacturing nano copper powder capable of providing nano-sized copper powder of high quality. means of solving the problem

[0005] One aspect of the present invention provides a method for producing nano copper powder, wherein the aqueous solution comprises a copper precursor; a copper ion complexing agent; a nonionic surfactant; a reaction activator selected from group 16 elements; and a reducing agent.

[0006] A method for manufacturing the nano copper powder according to one embodiment may include the step of manufacturing nano copper powder by reacting a first aqueous solution containing a copper precursor, a copper ion complexing agent, a nonionic surfactant, and a reaction activator with a second aqueous solution containing a reducing agent.

[0007] The above reaction activator may include sulfur (S), selenium (Se), or tellurium (Te).

[0008] The concentration of copper ions in the above aqueous solution may be 0.1 to 10 M.

[0009] The concentration of the reaction activator in the above aqueous solution may be 5 to 1,000 ppm.

[0010] The copper ions of the copper precursor and the reaction activator may be used in a molar ratio of 1:0.00002 to 1:0.04.

[0011] The average particle size of the above nano copper powder may be 10 nm to 2,000 nm.

[0012] The average particle size of the above nano copper powder may be 20 nm to 200 nm.

[0013] The copper ion complexing agent may include a carboxylic acid compound or a polyamine compound.

[0014] The above nonionic surfactant may include polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, polysorbate, carboxymethyl cellulose, gelatin, dextran, or xanthan gum.

[0015] The copper precursor may include CuSO4, Cu(NO3)2, or CuCl2.

[0016] The above reaction may be carried out at a temperature of 10 to 90 ℃ for 10 to 100 minutes. Effects of the invention

[0017] According to one embodiment of the manufacturing method, high-quality copper powder controlled to nano-size can be efficiently manufactured.

[0018] A manufacturing method of one embodiment can achieve a fast reaction rate and high yield for the synthesis of nano copper powder under mild reaction conditions. The nano copper powder produced therefrom can have a uniform particle distribution and can be effectively applied in various industrial fields, such as conductive paste for wiring and electronic components for Heterojunction Technology (HJT) solar cells, heat dissipation and bonding paste for power semiconductors for electric vehicles, via-fill paste for glass substrates for next-generation semiconductors, electromagnetic shielding, energy storage systems (ESS), and catalysts.

[0019] In addition, the manufacturing method of one embodiment is environmentally friendly and can improve productivity because it can produce nano copper powder under mild reaction conditions and in an aqueous environment. Brief explanation of the drawing

[0020] Figure 1 is an FE-SEM analysis image of the nano copper powder prepared in Example 1. Figure 2 is an FE-SEM analysis image of the copper powder prepared in Comparative Example 1. Specific details for implementing the invention

[0021] Unless otherwise defined in this specification, all technical and scientific terms have the same meaning as generally understood by those skilled in the art to which the present invention pertains. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.

[0022] The singular form used in this specification is intended to include the plural form unless specifically indicated otherwise in the context.

[0023] Throughout this specification, the terms “comprising,” “having,” “containing,” or “having” any component mean that, unless specifically stated otherwise, other components are not excluded but may be included, and do not exclude elements, materials, or processes not additionally listed.

[0024] The numerical ranges used herein include lower and upper limits and all values ​​within the range, increments logically derived from the form and width of the defined range, all of which are limited, and all possible combinations of upper and lower limits of the numerical range defined in different forms. Unless otherwise specifically defined in this specification, values ​​outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical range.

[0025] Unless otherwise specifically defined in this specification, “about” may be considered to be a value within 30%, 25%, 20%, 15%, 10%, or 5% of the specified value.

[0026] The present disclosure will be described in detail below. However, this is merely illustrative and the present disclosure is not limited to the specific embodiments described illustratively.

[0027] One aspect of the present invention provides a method for manufacturing nano copper powder capable of efficiently producing high-quality copper powder controlled to nano size.

[0028] A method for manufacturing nano copper powder according to one embodiment may use an aqueous solution comprising a copper precursor; a copper ion complexing agent; a nonionic surfactant; a reaction activator selected from group 16 elements; and a reducing agent.

[0029] Specifically, a method for manufacturing the nano copper powder according to one embodiment may include the step of manufacturing the nano copper powder by reacting a first aqueous solution containing a copper precursor, a copper ion complexing agent, a nonionic surfactant, and a reaction activator with a second aqueous solution containing a reducing agent.

[0030] A method for manufacturing nano copper powder according to one embodiment can provide nano-sized copper powder having a uniform particle distribution by satisfying the above composition combination, and can achieve a fast reaction rate and a high yield under mild reaction conditions.

[0031] For example, the above reaction may be carried out at a temperature of 10 to 90 ℃, or 50 to 90 ℃, or 60 to 90 ℃, or 60 to 80 ℃ for 10 to 100 minutes, or 10 to 80 minutes, or 10 to 60 minutes, or 20 to 40 minutes.

[0032] The above copper precursor may be used without limitation as long as it has high water solubility and can supply copper ions, and non-limiting examples may include Cu(II) precursors such as CuSO4, Cu(NO3)2, or CuCl2.

[0033] The shape of the nano copper powder produced by the method according to one embodiment is not particularly limited and may be, for example, spherical, elliptical, or angular amorphous. The spherical shape may include not only a perfect sphere in the conventional sense where the surface is substantially equidistant from the center, but also a round shape close to a sphere where no angles are formed. The angular amorphous shape is not particularly limited as long as the particle is angular, and may include, for example, polyhedral shapes selected from tetrahedrons, hexahedrons, octahedrons, etc.; and plate shapes, etc.

[0034] The average particle size of the nano copper powder produced by the method according to one embodiment may be 10 nm to 2,000 nm, or 20 nm to 1,000 nm, or 10 nm to 900 nm, or 20 nm to 800 nm, or 20 nm to 500 nm, or 20 nm to 300 nm, or 20 nm to 200 nm, and the average particle size of the nano copper powder may be controlled by the type of reaction activator, the molar ratio of copper ions to the reaction activator, the type of copper ion complexing agent, the molar ratio of copper ions to the complexing agent, the type of nonionic surfactant, the molar ratio of copper ions to the nonionic surfactant, or a combination thereof.

[0035] The above reaction activator may include sulfur (S), selenium (Se), tellurium (Te), or polonium (Po), and specifically may be sulfur, selenium, or tellurium.

[0036] With respect to the total aqueous solution above, the solid content may be used in an amount of 10 to 60 weight%, or 10 to 50 weight%, or 20 to 50 weight%, or 20 to 40 weight%, but is not limited thereto.

[0037] The concentration of copper ions in the above-mentioned aqueous solution may be 0.1 to 10 M, or 0.1 to 5 M, or 0.3 to 3 M, but is not limited thereto.

[0038] The concentration of the reaction activator in the total aqueous solution may be 1 to 1,000 ppm, or 5 to 1,000 ppm, or 5 to 500 ppm, or 5 to 300 ppm, or 10 to 200 ppm, but is not limited thereto.

[0039] The copper ions of the copper precursor and the reaction activator can be used in a molar ratio of 1:0.00002 to 1:0.04, specifically in a molar ratio of 1:0.0001 to 1:0.01, or in a molar ratio of 1:0.0001 to 1:0.005, or in a molar ratio of 1:0.0005 to 1:0.005, but are not limited thereto.

[0040] The copper complexing agent mentioned above may be used without limitation as long as it is a material capable of forming a coordination bond with copper ions, including a donor atom selected from O, N, S, and P, and may include, for example, carboxylic acid compounds or polyamine compounds.

[0041] The above carboxylic acid compounds may include single carboxylic acid compounds containing one carboxyl group, polycarboxylic acid compounds containing two or more carboxyl groups, hydroxycarboxylic acid compounds, or aminocarboxylic acid compounds, and may include, for example, formic acid, acetic acid, oxalic acid, citric acid, lactic acid, malic acid, ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA), aspartic acid and glutamic acid, lysine and arginine, etc.

[0042] The above polyamine compounds may include, for example, ethylenediamine, diethylenetriamine, diethylenetetraamine, triethylenetetraamine, pentaethylenehexaamine, hexamethylenediamine, etc.

[0043] The copper ions of the copper precursor and the copper ion complexing agent may be used in a molar ratio of 1:0.001 to 1:1, or a molar ratio of 1:0.001 to 1:0.1, or a molar ratio of 1:0.001 to 1:0.05, but are not limited thereto.

[0044] The above nonionic surfactants may be used without limitation as long as they are commonly used in the relevant technical field, and non-limiting examples may include polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, polysorbate, carboxymethyl cellulose, or gelatin, dextran, and xanthan gum.

[0045] The above nonionic surfactant may be used in an amount of 0.1 to 10 weight%, or 0.1 to 5 weight%, or 0.5 to 5 weight%, or 1 to 5 weight% with respect to the total aqueous solution, but is not limited thereto.

[0046] The above reducing agent may be used without limitation as long as it can reduce copper ions, and may be selected from hydrazine, NaBH4, LiBH4, formaldehyde, acetaldehyde, dextrose, glyoxal, and ascorbic acid as a non-limiting example.

[0047] The copper ions of the copper precursor and the reducing agent may be used in a molar ratio of 1:0.5 to 1:7, or 1:1 to 1:7, or 1:2 to 1:5, but are not limited thereto.

[0048] The above-described embodiment will be explained in more detail below through examples. However, the following examples are for illustrative purposes only and do not limit the scope of the claims.

[0049] [Example 1]

[0050] A first aqueous solution was prepared by dissolving 62.5g of CuSO45H2O, 15g of PVP(K-30), 0.23g of formic acid, and 5mL of a 1000ppm aqueous solution of tellurium (Te) in 245g of distilled water by stirring. A second aqueous solution was prepared by dissolving 150g of ascorbic acid in 250g of distilled water, raising the temperature of the first solution to 80℃, adding the second aqueous solution to the first aqueous solution, and stirring the reaction mixture for 30 minutes.

[0051] Afterwards, the reactants were precipitated, washed twice with distilled water and twice with ethanol, and vacuum dried at 50°C to produce nano copper powder.

[0052] Nano copper powder prepared using a field emission scanning electron microscope (FE-SEM) was observed. The longest diameter of 100 random copper particles was measured in the FE-SEM image, averaged, and rounded to the nearest ten (unit: nm) to determine the average particle size of the nano copper powder, and the average particle size of the nano copper powder in Example 1 was 100 nm.

[0053] [Example 2]

[0054] The above Example 1 was carried out in the same manner except that the amount of 1,000 ppm tellurium aqueous solution used to prepare the first solution was changed to 2.5 mL and the amount of distilled water used was changed to 247.5 g, and the average particle size of the prepared nano copper powder was confirmed to be 150 nm.

[0055] [Example 3]

[0056] The above Example 1 was carried out in the same manner except that the amount of 1,000 ppm tellurium aqueous solution used for preparing the first solution was changed to 10 mL and the amount of distilled water used was changed to 240 g, and the average particle size of the prepared nano copper powder was confirmed to be 70 nm.

[0057] [Example 4]

[0058] The above Example 1 was carried out in the same manner except that the amount of 1,000 ppm tellurium aqueous solution used to prepare the first solution was changed to 15 mL and the amount of distilled water used was changed to 235 g, and the average particle size of the prepared nano copper powder was confirmed to be 30 nm.

[0059] [Example 5]

[0060] The above Example 1 was carried out in the same manner except that sulfur (S) was used instead of tellurium, and the average particle size of the nano copper powder produced was confirmed to be 1,500 nm.

[0061] [Example 6]

[0062] The above Example 1 was carried out in the same manner except that selenium (Se) was used instead of tellurium, and the average particle size of the nano copper powder produced was confirmed to be 300 nm.

[0063] [Comparative Example 1]

[0064] The above Example 1 was carried out in the same manner except that tellurium was not used, and the average particle size of the copper powder produced was confirmed to be 10 μm.

[0065] As described above, the present disclosure has been explained by specific details and limited embodiments, but this is provided only to aid in a more comprehensive understanding of the present disclosure. The present disclosure is not limited to the above embodiments, and various modifications and variations are possible from this description by those skilled in the art to which the present disclosure pertains.

[0066] Accordingly, the present disclosure is not limited to the embodiments described above, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to be within the scope of the present disclosure.

Claims

Claim 1 A method for producing nano copper powder, comprising the step of producing nano copper powder by reacting a first aqueous solution containing a copper precursor, a copper ion complexing agent, a nonionic surfactant, and a reaction activator with a second aqueous solution containing a reducing agent, wherein the reaction activator is selected from sulfur (S), selenium (Se), or tellurium (Te), and the copper ions of the copper precursor and the reaction activator are used in a molar ratio of 1:0.00002 to 1:0.

04. Claim 2 delete Claim 3 delete Claim 4 A method for manufacturing nano copper powder according to claim 1, wherein the concentration of copper ions in the total aqueous solution is 0.1 to 10 M. Claim 5 A method for manufacturing nano copper powder according to claim 1, wherein the concentration of the reaction activator in the total aqueous solution is 1 to 1,000 ppm. Claim 6 delete Claim 7 A method for manufacturing nano copper powder according to claim 1, wherein the average particle size of the nano copper powder is 10 nm to 2,000 nm. Claim 8 A method for manufacturing nano copper powder according to claim 1, wherein the average particle size of the nano copper powder is 20 nm to 200 nm. Claim 9 A method for manufacturing nano copper powder according to claim 1, wherein the copper ion complexing agent comprises a carboxylic acid compound or a polyamine compound. Claim 10 A method for producing nano copper powder according to claim 1, wherein the nonionic surfactant comprises polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, polysorbate, carboxymethyl cellulose, gelatin, dextran, or xanthan gum. Claim 11 A method for producing nano copper powder according to claim 1, wherein the copper precursor comprises CuSO4, Cu(NO3)2, or CuCl2. Claim 12 A method for manufacturing nano copper powder according to claim 1, wherein the reaction is carried out at a temperature of 10 to 90 ℃ for 10 to 100 minutes.

Citation Information

Patent Citations

  • Copper nano-particles and preparation method thereof

    KR100790458B1

  • Preparation method of copper nanoparticles

    KR1020120045711A

  • Micro-nano copper powder and preparation method thereof

    CN106513696A

  • Aqueous-based method for preparing metal chalcogenide nanomaterials

    JP2018525304A